New insights into the regulation of cholesterol efflux from the sperm membrane - Tamara Leahy; Bart M Gadella (Asian Journal of Andrology, 2015)
Cholesterol is an essential component of the mammalian plasma membrane because it promotes membrane stability without comprising membrane fluidity. Given this important cellular role, cholesterol levels are tightly controlled at multiple levels. It has been clearly shown that cholesterol redistribution and depletion from the sperm membrane is a key part of the spermatozoon′s preparation for fertilization. Some factors that regulate these events are described (e.g., bicarbonate, calcium) but the mechanisms underlying cholesterol export are poorly understood. How does a hydrophobic cholesterol molecule inserted in the sperm plasma membrane enter the energetically unfavorable aqueous surroundings? This review will provide an overview of knowledge in this area and highlight our gaps in understanding. The overall aim is to better understand cholesterol redistribution in the sperm plasma membrane, its relation to the possible activation of a cholesterol transporter and the role of cholesterol acceptors. Armed with such knowledge, sperm handling techniques can be adapted to better prepare spermatozoa for in vitro and in vivo fertilization.